Tuning of n-type doping by intercalation of group V and VII atoms in SnS2 bilayer. (July 2022) - Miloudi, Mohammed El Amine; Liu, Yong; Ge, Yanfeng; Ouadah, Ouahiba
Abstract: Doping with group V and VII atoms is an excellent approach for altering the electronic structures and improving optical properties. Using density functional theory, we have systematically examined the fundamental properties of the AA-SnS2 bilayer doped with N, P, As, F, Cl, Br, and I. We investigated the stability of doped systems based on formation energies, where interstitial doping is energetically more stable in the tetrahedral sites for N, P, F, and in the octahedral ones. At the same time, the latter is more favorable for As, Cl, and Br. Furthermore, transition level calculations indicated that N, P, As, F, Cl, Br, and I impurities can provide efficacious n-type holders in the AA-SnS2 bilayer for all doped systems. In addition, optical studies have shown that doping with group V and VI atoms can modify the absorption and reflectivity of the AA-SnS2 bilayer. The pure and doped systems are promising materials for optoelectronic applications and can be ideally used in the UV region.